Molecular Characterization of Olive (Olea europaea L.) Cultivars in Duhok Governorate - Abdullah, Bekas Jameel; Ali, Avesta Mohammed (Science Journal of University of Zakho, 2022)
The olive tree (Olea europaea L.) was considered one of the most cultivated crops in the Mediterranean region, and it had an economically important value due to it began consumed as a table olive and oil production. In this study, AFLP and SRAP techniques were used to identify 15 cultivars of olive plants that were collected from 12 different locations in the Duhok governorate, eleven primer combinations of sequence-related amplified polymorphism (SRAP) and ten primer combinations of amplified fragment length polymorphism (AFLP) were used to fingerprinting these cultivars. The results show that the SRAP marker had the least genetic distance 0.241between (Shtla falay olive and Khodeiri olive) and the highest value 0.946 was found between (Zawita olive and Sorani olive). While AFLP marker show the lowest value of 0.107 between (Nzarky olive and Dger olive) and the highest value of 0.916 between (Amedi olive and Shtla falay olive). Cluster analysis based on AFLP and SRAP combined data clearly differentiated the genotype and it showed it was a powerful tool to evaluate the genetic distance and fingerprinting of these tested cultivars. Establishing the genetic relationships between cultivars and species, and the construction of genetic maps, had the main aims for the researchers in plant breeding programs and to understand the plant evolution lingues, and as a conclusion, this study demonstrates that AFLP and SRAP markers both are powerful tools in plants tree genetics.